Genetic variants in the vitamin D pathway genes VDBP and RXRA modulate cutaneous melanoma disease‐specific survival. (29th January 2016) - Yin, Jieyun; Liu, Hongliang; Yi, Xiaohua; Wu, Wenting; Amos, Christopher I.; Fang, Shenying; Lee, Jeffrey E.; Han, Jiali; Wei, Qingyi
Summary: Single nucleotide polymorphisms (SNPs) in the vitamin D pathway genes have been implicated in cutaneous melanoma (CM) risk, but their role in CM disease‐specific survival (DSS) remains obscure. We comprehensively analyzed the prognostic roles of 2669 common SNPs in the vitamin D pathway genes using data from a published genome‐wide association study (GWAS) at The University of Texas M.D. Anderson Cancer Center (MDACC) and then validated the SNPs of interest in another GWAS from the Nurses' Health Study and Health Professionals Follow‐up Study. Among the 2669 SNPs, 203 were significantly associated with DSS in MDACC dataset (P   <   0.05 and false‐positive report probability < 0.2), of which 18 were the tag SNPs. In the replication, two of these 18 SNPs showed nominal significance: the VDBP rs12512631 T > C was associated with a better DSS [combined hazards ratio (HR) = 0.66]; and the same for RXRA rs7850212 C > A (combined HR = 0.38), which were further confirmed by the Fine and Gray competing‐risks regression model. Further bioinformatics analyses indicated that these loci may modulate corresponding gene methylation status.